Unveiling Diabetes Risk Factors and Screening Deficits in Majalengka Indonesian Pilgrims - Rustika Rustika; Asep Kusnali; Siti Romlah Setiawangsih; Anton Suryatma; Jane Kartika Propiona; Ristrini Ristrini; Dede Anwar Musadad; Joko Irianto; Basuki Rachmat; Wawan Ridwan; Early Wulandari Muis; Sarah Handayani; Nurul Huriah Astuti (Jurnal Ilmu Kesehatan Masyarakat, 2025)
Diabetes mellitus (DM) poses significant health risks for hajj pilgrims due to physical stress, environmental exposure, and limited access to acute care during pilgrimage. In Indonesia, DM prevalence among prospective pilgrims is rising, yet empirical evidence on its predictors remains limited. This study aimed to identify demographic and clinical predictors of DM among hajj pilgrims from Majalengka District, West Java, using data from the 2024 Integrated Hajj Computerised System for Health Sector. A cross-sectional analysis was conducted on 1,140 pilgrims undergoing istithaah health screening. Variables included age, gender, BMI, abdominal obesity, blood pressure, lipid profiles, and family medical history. Descriptive statistics, Chi-square tests, and multivariate logistic regression were employed to examine associations with DM status. Older age (40–60 and >60 years), abdominal obesity, elevated triglyceride levels, and a family history of diabetes were significantly associated with increased odds of DM. In contrast, BMI and gender were not statistically significant predictors. Pilgrims who met the istithaah criteria had significantly lower prevalence of DM, supporting the effectiveness of current screening measures. However, gaps in consistent implementation remain. This study underscores the need to strengthen metabolic risk assessments in pre-hajj screenings by incorporating abdominal obesity and lipid profile measurements alongside conventional indicators. The findings support policy refinement in the istithaah process, including standardisation across districts and enhanced digital integration through Siskohatkes. These improvements are vital to safeguard pilgrims’ health and advance non-communicable disease prevention in Indonesia.